2010
DOI: 10.1016/j.mcn.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

High content screening of cortical neurons identifies novel regulators of axon growth

Abstract: Neurons in the central nervous system lose their intrinsic capacity for axon regeneration as they mature, and it is widely hypothesized that changes in gene expression are responsible. Testing this hypothesis and identifying the relevant genes has been challenging because hundreds to thousands of genes are developmentally regulated in CNS neurons, but only a small subset are likely relevant to axon growth. Here we used automated high content analysis (HCA) methods to functionally test 743 plasmids encoding dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 58 publications
5
125
0
Order By: Relevance
“…In accordance with an inhibitory role of KLF4 in controlling axonal regeneration of cultured retinal ganglion cells or cortical neurons (3,27), we revealed that enhanced expression of KLF4 in vivo significantly abolished neurite outgrowth and radial migration of developing neurons. Conversely, its downregulation by shRNA drastically enhanced the polarity of migrating neurons by increasing the length of leading and trailing processes.…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with an inhibitory role of KLF4 in controlling axonal regeneration of cultured retinal ganglion cells or cortical neurons (3,27), we revealed that enhanced expression of KLF4 in vivo significantly abolished neurite outgrowth and radial migration of developing neurons. Conversely, its downregulation by shRNA drastically enhanced the polarity of migrating neurons by increasing the length of leading and trailing processes.…”
Section: Discussionsupporting
confidence: 79%
“…KLF7 and the closely related KLF6 enhance neurite outgrowth when overexpressed in cultured RGCs or cortical neurons (21,22), but their potential for promoting axon growth in the adult CNS remains unexplored. We focused on KLF7, based on its larger effects in vitro (22).…”
Section: Resultsmentioning
confidence: 99%
“…In the CST, overexpression of the neurotrophin receptor TrkB enables regeneration into subcortical BDNF-secreting tissue grafts, and, notably, knockout of PTEN evokes regeneration in the spinal cord (19,20). The regenerative response evoked by these gene manipulations, including PTEN knockout, remains incomplete in terms of both the distance traveled by regenerating axons and the percent of neurons that respond to treatment.These findings illustrate the critical need to develop additional tools to enhance the intrinsic growth state of CNS neurons.We recently identified the Krüppel-like factors (KLFs), a 17-member family of zinc finger transcription factors, as regulators of CNS axon regeneration (21,22). Knockout of one family member, KLF4, promotes axon regeneration by retinal ganglion cells (RGCs) in vivo, demonstrating that KLF family members can act as neuron-intrinsic suppressors of axon growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation and image acquisition have been automated and several software applications are available for image analysis to obtain quantitative information from the cells. In academia HCS is mainly used in siRNA and cDNA screens to identify genes and proteins involved in specific pathways and processes (Blackmore et al, 2010;Neumann et al, 2010;Pelkmans et al, 2005 as examples). siRNA screens are performed also in pharmaceutical companies for target identification.…”
Section: Introductionmentioning
confidence: 99%